Is virtual cardiology training here to stay in the post-COVID era?. (14th October 2021) - Luther, V; Kailey, B; Dev, D S
Abstract: Background: In April 2020, face-face UK cardiology training was paused due to COVID-19. We adapted by utilising a video-conferencing platform to continue some form of education on a national scale (CardioWebinar). We studied the effectiveness of delivering virtual Cardiology education 1 year into the COVID pandemic. Methods: Expert speakers throughout the UK were sought after via social media and "word of mouth". Weekly webinars were organised and advertised (Canva posters) on social media (Twitter), as well as via the British Cardiovascular Society and British Junior Cardiologists' Association (BJCA) media links. Each webinar was scheduled mid-week at 17:30 (UK). Interested attendees registered for free using an online ticketing platform (Eventbrite). Webinars were delivered using an online video conferencing platform (Zoom) which required a £14.99 monthly subscription. Each webinar consisted of a 40-minute presentation followed by Q&A (20mins). All webinars were recorded and later accessible for free on the BJCA TV Gallery. A Learning Management System (LMS) collected feedback after each session and generated certificates of attendance. We systematically reviewed the LMS feedback from 6 consecutive webinars delivered between Jan-Feb 2021. We further surveyed our most recent (March 2021) attendees via an extended questionnaire exploring their experiences of our virtual education. Results: 55 CardioWebinars have been delivered since April 2020. The speakers have been predominantly Consultant Cardiologists from the UK. Some of the recordings have had >1000 views. Other than the video platform subscription, no cost was incurred in the delivery of this entire programme. We collected feedback from 392 respondents (∼65 live attendees per webinar) from each session between Jan-Feb 2021. The sessions were rated as "very good-excellent" by 97%. We collected a further 145 extended responses from March 2021 attendees. 90% rated the whole series as "very good –excellent" in supporting their cardiology education during the Covid pandemic, and 84% felt the programme sufficiently covered even the more challenging areas of the curriculum (e.g. aortopathies). 90% of the respondents felt that their work-life schedule allowed them to join the live webinars. The respondents where predominantly from the UK (91%), though included an international audience (9%). Whilst 74% of attendees were cardiology trainees, the remaining 26% included physiologists, nurses, consultants and other junior doctors. 99% felt that virtual education should continue to play a formal part in their training after the COVID pandemic. Conclusion: Webinars allow everyone interested in cardiac care across the world the opportunity to hear experts teach, and without a travel cost. They are cheap and easy to organise. This study suggests that webinars will remain an integral part of the post-COVID era. Funding Acknowledgement: Type of funding sources: None.